2020
DOI: 10.3847/1538-3881/ab7cd5
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Neptune’s Unusual Satellites from a Planetary Encounter

Abstract: The Neptunian satellite system is unusual, comprising Triton, a large (∼ 2700 km) moon on a close-in, circular, yet retrograde orbit, flanked by Nereid, the largest irregular satellite (∼300 km) on a highly eccentric orbit. Capture origins have been previously suggested for both moons. Here we explore an alternative in-situ formation model where the two satellites accreted in the circum-Neptunian disk and are imparted irregular and eccentric orbits by a deep planetary encounter with an ice giant (IG), like tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…In a similar sense, if Neptune's semimajor axis changes by a significant fraction of an au in a single encounter when it is approximately 28 au, objects previously trapped in mean motion resonance with Neptune can be dropped, forming the so-called kernel (Petit et al 2011) of the Kuiper belt (Nesvorný 2015;Deienno et al 2017), a pileup of orbits at ∼44 au with low eccentricities and inclinations 1 . Then, as mentioned already, Li & Christou (2020) showed that both Triton and Nereid, if formed in the circum-Neptunian disc, could be simultaneously put on evolutionary paths towards their observed orbits by the encounter (see also Harrington & Van Flandern 1979).…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…In a similar sense, if Neptune's semimajor axis changes by a significant fraction of an au in a single encounter when it is approximately 28 au, objects previously trapped in mean motion resonance with Neptune can be dropped, forming the so-called kernel (Petit et al 2011) of the Kuiper belt (Nesvorný 2015;Deienno et al 2017), a pileup of orbits at ∼44 au with low eccentricities and inclinations 1 . Then, as mentioned already, Li & Christou (2020) showed that both Triton and Nereid, if formed in the circum-Neptunian disc, could be simultaneously put on evolutionary paths towards their observed orbits by the encounter (see also Harrington & Van Flandern 1979).…”
Section: Introductionmentioning
confidence: 61%
“…The peculiarity of the Neptunian moon system does not stop at Triton. As discussed in Li & Christou (2020), the irregular satellite Nereid has the highest eccentricity among all Solar System moons and a relatively tight orbit deep inside Neptune's Hill radius (compared to other irregulars). If captured from the primordial planetesimal disc (Nesvorný et al 2007), Nereid would be the largest object captured by the giant planets (among Trojans and irregular satellites) from this reservoir during the instability period of the Nice scenario.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations